2019
DOI: 10.1101/858241
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-wide Association Study of Pediatric Obsessive-Compulsive Traits: Shared Genetic Risk between Traits and Disorder

Abstract: This study examined the genetic correlates of obsessive-compulsive (OC) traits and their shared genetic risks with obsessive-compulsive disorder (OCD). We conducted genome-wide association analyses on OC traits in 5018 unrelated Caucasian children and adolescents. Overall OC traits and trait dimensions (e.g., cleaning/contamination) were measured with the Toronto Obsessive-Compulsive scale (TOCS). One locus tagged by rs7856850 in an intron of PTPRD (protein tyrosine phosphatase δ) was associated with OC traits… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 68 publications
(85 reference statements)
1
12
0
Order By: Relevance
“…Polygenic risk score (PRS) (see Box) analyses performed in the three population samples discussed above provide an alternative approach to test the genetic correlation between subclinical OCS and clinical OCD. Using this method, PRS trained on genetic associations from OCS in the Burton et al [20] sample were associated with OCD case/control status in an independent sample of OCD cases and controls (Nagelkerke's pseudo R² = 0.28%, p = 0.0045) [23]. This association also held true when reversing the analysis and predicting population-based OCS using PRS trained on associations from OCD case/control GWAS studies.…”
Section: Heritability Of Ocsmentioning
confidence: 87%
See 4 more Smart Citations
“…Polygenic risk score (PRS) (see Box) analyses performed in the three population samples discussed above provide an alternative approach to test the genetic correlation between subclinical OCS and clinical OCD. Using this method, PRS trained on genetic associations from OCS in the Burton et al [20] sample were associated with OCD case/control status in an independent sample of OCD cases and controls (Nagelkerke's pseudo R² = 0.28%, p = 0.0045) [23]. This association also held true when reversing the analysis and predicting population-based OCS using PRS trained on associations from OCD case/control GWAS studies.…”
Section: Heritability Of Ocsmentioning
confidence: 87%
“…LDSC analysis allows the use of summary results in tests of genetic correlation (see Box). Burton et al [20] reported a high but statistically underpowered genetic correlation between OCD and OCS (r G = 0.83, SE = 0.43, p = 0.073) [23], whereas Smit et al did not find a genetic correlation between OCD and OCS as a general measure (incorporating both obsessive and compulsive symptoms jointly) but did find a significant genetic correlation between OCD and one of two subscale measures of OCS (the compulsion subscale; r G = 0.61, p = 0.017) [78].…”
Section: Heritability Of Ocsmentioning
confidence: 99%
See 3 more Smart Citations